2021
DOI: 10.18295/squmj.2021.21.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Insights Towards Patient Safety

Abstract: Objectives: This study aimed to explore Saudi Arabian medical students’ perceptions of patient safety. Methods: A cross-sectional descriptive study was conducted in the College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia, in September 2019. The Attitudes to Patient Safety Questionnaire (APSQ III) was used to explore undergraduate medical students’ attitudes towards and knowledge of PS. The main outcomes measured were the APSQ III’s nine domains. Data were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, two other studies that were conducted among medical students in Saudi Arabia and Pakistan revealed that "Team functioning" had the highest mean scores (Kamran, Bari, Khan, & Al-Eraky, 2018;Alshahrani et al, 2021). This can be explained by the difference of the population among the studies as medical students might not be aware of the magnitude of longer work hours on performance when compared to practicing health professionals.…”
Section: Attitudes Toward Patient Safetymentioning
confidence: 94%
“…However, two other studies that were conducted among medical students in Saudi Arabia and Pakistan revealed that "Team functioning" had the highest mean scores (Kamran, Bari, Khan, & Al-Eraky, 2018;Alshahrani et al, 2021). This can be explained by the difference of the population among the studies as medical students might not be aware of the magnitude of longer work hours on performance when compared to practicing health professionals.…”
Section: Attitudes Toward Patient Safetymentioning
confidence: 94%
“…Research indicates a positive correlation between the level of education on patient safety and the knowledge and attitudes towards it, with medical schools worldwide adopting various pedagogical approaches, such as lectures, workshops, and heuristic exercises, to disseminate essential information on the subject. A positive outlook on patient safety has been observed among medical undergraduate students, highlighting an optimistic trend in education on this vital topic (6)(7)(8). For instance, a cross-sectional survey at Dow Medical College, a leading medical institution in Pakistan, revealed that while a majority of undergraduate medical students supported the notion that medical errors should be reported, a significant number also believed that reporting errors does not necessarily prevent future occurrences.…”
Section: Introductionmentioning
confidence: 99%